CALCULATION OF THE PARAMETERS OF CLEANER FROM COTTON FINE WASTE (Web of Technology: Multidimensional Research Journal, 2024)
The article presents the construction scheme and principle of operation of the machine for cleaning cotton from small waste with drums with multi-faceted piles. Based on theoretical studies, the results of justification of cleaner parameters are given. Recommendations for the use of a cotton cleaner from small impurities recommended for production are given.